Effectiveness of Information Booklet on Knowledge of Father about his Contribution Related to Menarche of the Daughter in Selected Rural Area - Chakor, Ganesh; Avinash Deshpande, Rupali; Gurav, Arundhati; Naik, Pournima; Shinde, Ekta; Morane, Dharmaraj (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The main aim of the present study was “Effectiveness of Information Booklet on knowledge of father about his contribution related to menarche of the daughter in selected rural area.” Background: The age of menarche or first menstruation is an important maturity indicator for assessment of development status of pubertal female. Puberty is a very important development stage for females. It involves a complex process of biological, morphological, and psychological changes that transform the body from that of child to adult. In female puberty is a slow process. During this time, female experiences their first menstrual bleeding known as menarche. Materials and Methods: A quantitative approach with pre experimental one group pre-test post-test design was used for the study. A total of 100 father were selected as sample for study using purposive sampling technique. Inform consent was taken from father. Pre-test was conducted using structured knowledge questionnaire and on the same day Information Booklet was also administered. After 7 days, post-test was conducted to assess the gained in knowledge using the same structured knowledge questionnaire to assess post-test knowledge of father. Data were analyzed with the help of frequency, mean and standard deviation. Chi-square was used to determine the association between knowledge of father regarding menarche of the daughter with selected demographic variables. Results: Study Findings revealed that majority of the father that is 87% were having one biological daughter in the family, 10% of father were having two biological daughter in the family, and 3% were having three biological daughter in the family. Majority of the father that is 94% were do not known when girls start their first menstruation and remaining 6% of father were know when girls start their first menstruation. About 99% represented that from wife they know about menstrual cycle and 1% of father were receive information from mass media about menstrual cycle. About 100% father show interest that they wanted to know about menstrual cycle and there was a significant association between the occupation were found significant at (<0.05) level of significance. Conclusion: There was significant difference in the pre-test and post-test knowledge score of father, which indicated Information Booklet was effective in improving knowledge of father on his contribution related of the daughter. The administration of Information Booklet acts as guiding key for father to improve knowledge and aware themes self about daughter menstruation.